THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE (TPR) METHOD TO IMPROVE STUDENTS’ VOCABULARY: Abstract, Introduction, Literature Review, Method, Findings and Discussion, References - Faridatus Salma; Khoirul Wafa; Faridatus Salma; Khoirul Wafa (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2024)
This research aims to determine how the implementation of teaching vocabulary using the TPR method and whether the TPR method can improve the students’ vocabulary. This type of research was classroom action research (CAR). The research was conducted in two cycles. The research subjects were 20 students. Data collection was obtained based on observation, test, and documentation results. The data analysis used is descriptive qualitative and descriptive quantitative. Based on the qualitative data analysis, it shows that the implementation of the TPR method can make students easier to remember vocabulary. The results of the quantitative data analysis showed that the percentage of pre-action scores was 30% of students who passed. After carrying out actions using the TPR method in the learning process, cycle I data increased by 15% to 45% of students who passed. In cycle II, 80% of students passed the test and an increase of 35%. Cycle II was stopped because students had achieved classical mastery 80%/16 of the total number of students in one class, and individual students reached KKM 75. From this data, it can be concluded that the learning was declared complete individually and classically. So, using the TPR method can improve students’ vocabulary.This research aims to determine how the implementation of teaching vocabulary using the TPR method and whether the TPR method can improve the students’ vocabulary. This type of research was classroom action research (CAR). The research was conducted in two cycles. The research subjects were 20 students. Data collection was obtained based on observation, test, and documentation results. The data analysis used is descriptive qualitative and descriptive quantitative. Based on the qualitative data analysis, it shows that the implementation of the TPR method can make students easier to remember vocabulary. The results of the quantitative data analysis showed that the percentage of pre-action scores was 30% of students who passed. After carrying out actions using the TPR method in the learning process, cycle I data increased by 15% to 45% of students who passed. In cycle II, 80% of students passed the test and an increase of 35%. Cycle II was stopped because students had achieved classical mastery 80%/16 of the total number of students in one class, and individual students reached KKM 75. From this data, it can be concluded that the learning was declared complete individually and classically. So, using the TPR method can improve students’ vocabulary.